USULAN PERBAIKAN STRATEGI BISNIS DI SLAYER COFFEE MEDAN DENGAN METODE BUSINESS MODEL CANVAS (BMC) - Margie Subahagia Ningsih,; Rizkha Rida,; Ragel Maulana, (Journal of Innovation Research and Knowledge, 2025)
Slayer Coffee Medan is a coffee shop located in Medan City that operates in the beverage industry focusing on processed coffee beverage products. The problems that occur at Slayer Coffee Medan are management and marketing. Slayer Coffee Medan was established in 2020, therefore it does not yet have business management and development using the BMC method and SWOT analysis which are used as analysis for management and marketing development. The conclusion of this study is based on the Business Model Canvas analysis with SWOT analysis that can be applied to Slayer Coffee Medan including the elements of Customer Segment, Value Propositions, Customer Relationships, Revenue Streams, Key Resources, Key Partnerships and Cost Structure